Role of calcium channel subtypes in calcium transients in hippocampal CA3 neurons - Elliott, EM (J Neurosci, 1995)
Multiple subtypes of voltage-gated calcium channels are differentially localized in brain neurons suggesting that they serve distinct roles in neuronal excitation and signaling. In organotypic hippocampal slice cultures, class D (L-type) calcium channels are predominantly located in the cell bodies of CA3 neurons while class B (N-type) and class A (P or Q-type) are localized in dendrites and associated presynaptic terminals with relatively low somal expression. Using specific antagonists to inhibit calcium transients recorded in CA3 neuronal cell bodies, we found that L-type calcium channels have a predominant role in somal calcium transients elicited by trains of strong stimuli applied to either the soma or the distal apical dendrite while class A calcium channels make a smaller contribution. Presynaptic class B (N- type) and class A (P- and/or Q-type) calcium channels are critical for glutamate-mediated synaptic transmission onto the dendrites of CA3 neurons. Postsynaptic class A and B calcium channels detected on the dendritic shaft by immunocytochemistry were not found to contribute substantially to somal calcium transients during repetitive stimulation of distal dendrites, but sodium channels were required for calcium transients elicited by somatic or dendritic stimulation. Our results show that the different calcium channel subtypes serve distinct roles in cellular activation and transmission of signals in CA3 neurons, consistent with their differential subcellular localization.